The role of transforming growth factor-ß (TGF-ß1) in postmenopausal women with pelvic organ prolapse: An immunohistochemical study. (July 2020) - Carlin, Greta Lisa; Bodner, Klaus; Kimberger, Oliver; Haslinger, Peter; Schneeberger, Christian; Horvat, Reinhard; Kölbl, Heinz; Umek, Wolfgang; Bodner-Adler, Barbara
Abstract: Objective: Aim of the study was to investigate the expression of transforming growth factor-β1 (TGF-β1), a key regulator of the extracellular matrix composition, in the uterosacral ligaments (USLs) of women with pelvic organ prolapse (POP) compared with controls. We hypothesized that the expression pattern of TGF-β1 differs between postmenopausal women with or without POP. Methods: Under ethical approval, USL samples were obtained from postmenopausal women undergoing vaginal hysterectomy for stage two or greater pelvic organ prolapse (cases, n = 70) and from postmenopausal women without pelvic organ prolapse undergoing vaginal hysterectomy for benign indications (controls, n = 30). Immunohistochemical staining was performed from paraffin embedded tissue using anti-TGF-β1 antibodies. The expression of TGF-β1 was evaluated by the pathologist, who was blinded to all clinical data. Results: The expression of TGF-ß1 was similar in patients with symptomatic POP (89 % positive) and in controls (90 % positive) without any signs of prolapse (p = 0.091). Age-adjusted analysis did not significantly alter these results. Regarding POP-Q stages, TGF-ß1 was significantly more frequently expressed in severe prolapse cases compared to moderate/mild cases (POP-Q stage IV versus POP-Q stage II and III; p = 0.001). No significant association could be detected between TGF-ß1 expression and age, BMI and parity in cases with POP (p > 0.05). As published previously, advanced patients' age as well as early menopausal age remained independent risk factors associated with POP in multiple logistic regression analysis (p = 0.001; p = 0.02). Conclusion: Although our study detected POP-Q stage related alterations in USL composition and TGF-ß1 expression, there was no significant difference in the expression of TGF-β1 in cases with or without prolapse.